Water-assisted rapid growth of monolayer graphene films on SiO2/Si substrates. (July 2019) - Wei, Shijing; Ma, Lai-Peng; Chen, Mao-Lin; Liu, Zhibo; Ma, Wei; Sun, Dong-Ming; Cheng, Hui-Ming; Ren, Wencai
Abstract: Metal-free growth of high-quality monolayer graphene films by chemical vapor deposition (CVD) on dielectric substrates is of great significance for the development of high-performance graphene-based electronic and optoelectronic devices. However, the existing CVD processes suffer from poor structural uniformity (or growth quality) and/or a slow growth rate due to the negligible catalytic activity of dielectric substrates. Here, we report a water-assisted CVD process for rapid growth of monolayer graphene film on SiO2 /Si substrate without using metal catalysts or ultra-high temperature. Even trace amount of water enables the preferential formation of monolayer graphene films with significantly reduced structural defects. Particularly, this strategy enables the rapid growth of monolayer graphene by effectively lowering the growth kinetic barrier. We attribute the benefits of water on simultaneously improving the structural uniformity and growth rate to its mild oxidative effect and the role in accelerating the release of oxygen from the SiO2 /Si substrate, respectively. Our work provides helpful information for efficient and controllable CVD growth of high-quality graphene on dielectric substrates. Graphical abstract: Image 1